The economic evaluation of irrigation with particular reference to water harvesting systems : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Agricultural Economics and Farm Management at Massey University - Sorrenson, William Jack (Massey University, 1977)
1.1 BACKGROUND AND OBJECTIVES This study is concerned with economic evaluations of irrigation systems, particularly those based on water harvesting. While problems associated with the development of irrigation projects and allocation of irrigation water are usually diverse and complex, it is well recognised that these problems can be usefully studied within the framework of economic theory. This is well illustrated by the widespread adoption of cost-benefit analysis since the 1950's in New Zealand (N.Z.) and many other countries, in evaluating public investment in irrigation and other water resource development projects. The continuing expansion of irrigation and increasing competition for water between urban, industrial and rural users, indicate that economists should play an important role in evaluating irrigation systems. Economic investigations of water harvesting irrigation systems are of particular importance in this context since water harvesting may provide the only, or cheapest, source of water to an area, and also because water that may otherwise be lost, primarily to the sea, is harvested and utilised.
Keywords: New Zealand; Irrigation -- Economic aspects; Water harvesting; Research -- Mathematical models